Variation in Communication of Competing Risks of Mortality in Prostate Cancer Treatment Consultations. Issue 2 (4th August 2022) - Daskivich, Timothy J.; Gale, Rebecca; Luu, Michael; Naser-Tavakolian, Aurash; Venkataramana, Abhi; Khodyakov, Dmitry; Anger, Jennifer T.; Posadas, Edwin; Sandler, Howard; Spiegel, Brennan; Freedland, Stephen J.
Abstract : Purpose: Men with prostate cancer prefer patient-specific, quantitative assessments of longevity in shared decision making. We sought to characterize how physicians communicate the 3 components of competing risks—life expectancy (LE), cancer prognosis and treatment-related survival benefit—in treatment consultations. Materials and Methods: Conversation related to LE, cancer prognosis and treatment-related survival benefit was identified in transcripts from treatment consultations of 42 men with low- and intermediate-risk disease across 10 multidisciplinary providers. Consensus of qualitative coding by multiple reviewers noted the most detailed mode of communication used to describe each throughout the consultation. Results: Physicians frequently failed to provide patient-specific, quantitative estimates of LE and cancer mortality. LE was omitted in 17% of consultations, expressed as a generalization (eg "long"/"short") in 17%, rough number of years in 31%, probability of mortality/survival at an arbitrary timepoint in 17% and in only 19% as a specific number of years. Cancer mortality was omitted in 24% of consultations, expressed as a generalization in 7%, years of expected life in 2%, probability at no/arbitrary timepoint in 40% and in only 26% as the probability at LE. Treatment-related survival benefit was often omitted; cancer mortality was reported without treatment in 38%, with treatment in 10% and in only 29% both with and without treatment. Physicians achieved "trifecta"—1) quantifying probability of cancer mortality 2) with and without treatment 3) at the patient's LE—in only 14% of consultations. Conclusions: Physicians often fail to adequately quantify competing risks. We recommend the "trifecta" approach, reporting 1) probability of cancer mortality 2) with and without treatment 3) at the patient's LE.